Therapy with Interleukin-22 Alleviates Hepatic Injury and Hemostasis Dysregulation in Rat Model of Acute Liver Failure - Tariq Helal Ashour (Advances in Hematology)
The therapeutic efficacy of interleukin-22 (IL-22) on liver injury and hematological disturbances was studied in rat model of acute liver failure (ALF) induced by D-galactosamine/lipopolysaccharide (D-GalN/LPS). The following parameters were investigated: (1) survival rate, (2) serum levels of liver function enzymes (aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP)), total bilirubin (TBILI), and total albumen (ALB), (3) blood clotting tests (prothrombin time (PT), activated partial thromboplastin time (aPTT), and fibrinogen level (FIB)) and white blood cells (WBCs), red blood cells (RBCs), and platelet counts, (4) hepatic levels of tumor necrosis factor-α (TNF-α) and cyclooxygenase-2 (COX-2), and (5) liver histopathology. After 48 hours of D-GalN/LPS, the rats exhibited 20% mortality, significant increases in AST, ALT, ALP, TBILI, PT, and aPTT, TNF-α, and COX-2 and significant decreases in FIB, WBCs, and RBCs. By contrast, therapy with IL-22 prevented the lethal effect of D-GalN/LPS by 100% and efficiently alleviated all the biochemical and hematological abnormalities that were observed in ALF untreated group. Furthermore, IL-22 treatment decreased the hepatic contents of TNF-α and COX-2. The histopathological findings also supported the hepatoprotective effect of IL-22. Taken together, therapy with IL-22 can represent a promising therapeutic tool against liver injury and its associated hemostasis disturbances.